Man’s animality in the light of st. Augustine’s philosophical works - Terka, Mariusz (Vox Patrum, 2018)
As a corporeal being, man is part of the material world, he lives and is subject to processes similar to those which prevail in the world of animals and exceeds them only owing to the fact that he possesses a rational soul. Thus, although a body makes animality possible for a man to exist and function, its nature, meaning man’s similarity to animals, is defined mainly by the relationship between the soul and body. Since animals do not have minds, animality understood on the ontological level is something man and animals share in common. St. Augustine describes this as experiencing bodily sensations by the sensual being, which, because of their turning towards material things, lives in the world of bodily sensations and finds their place in it. Therefore, this is irrational delectation in bodily matters. This animality in humans is also considered as a possible lifestyle, which means it is an object of the will’s choice and assumes the form of the process of becoming similar to animals in the moral sense. It consists in the fact that man, who is created in the image and likeness of God, being turned to Him by nature, yet due to the sin of pride turns away from Him and from contemplation of eternal truths, and because of covetousness goes towards the carnal world. Being pleased with worldly possessions and directing his desires towards them, man becomes accustomed to existing among corporeal matters, forgetting about God and his own nature, and aspires to sensual pleasures. Therefore, the consequence of turning away from the Creator and lustfully turning to worldly possessions is blindness that leads him or her into slavery of corporeality and idolatry.